Assistance in Making NIB for Micro Business UMKM in Gemurung Village - Panca Aprilia Rizky; Erika Damayanti; Vinna Gayuh Asih; Chabibahtus Sa'diyah; Nafia Ilhama Qurratu’aini; Luiza Gabunia (Yayasan Cendekiawan Digital Indonesia, 2025)
Sidoarjo is a city with over 171,000 MSME units, reflecting significant economic potential. However, maximizing this potential requires a strategic approach, particularly through business legality facilitated by the Business Identification Number (NIB). NIB not only provides access to financing but also strengthens consumer trust, expands market opportunities, and fosters collaborations with larger businesses. This study aimed to socialize and assist MSME actors in Gemurung Village, Gedangan District, Sidoarjo Regency, in understanding and managing NIB through the Online Single Submission (OSS) system developed by the Indonesian government. The methods applied included direct observation, educational sessions, and hands-on assistance in the NIB registration process. The results demonstrate that business legality through NIB significantly enhances MSME competitiveness and scalability. Several assisted business actors successfully obtained NIB and experienced increased consumer trust, broader market reach, and improved business prospects. This initiative serves as a replicable model for other regions, ultimately strengthening the national economy by integrating MSMEs into the formal business ecosystem.